La autoestima y logros de los aprendizajes en el área personal social en niños y niñas de cinco años de la Institución Educativa Inicial N° 657 Niños del Saber, Punchana 2022 - Alvarez Pinedo, Christie Jonelle (2022)
This research was carried out in this present year 2022 with the of relating esteem and learning achievements in the Personal Social area in five-year-old children of the Educational Institution N°657 Niños del Saber, 2022 - Punchana, located in the District of Punchana. The methodology used for this purpose was relational research, with a field and cross-sectional design. The population for this study consisted of 90 five-year-old children and the sample consisted of 60 children. The observation technique was also used and the Observation Form was applied as an instrument for data collection. Given that X2 c = 45.42 > X2 t = 3.84, it can be affirmed that there is a significant relationship between self-esteem and learning achievements in the personal-social area in 5-year-old children of the Educational Institution N°657 "Niños del Saber" 2022 - Punchana.